Children at high risk - Virginia Association for Retarded Citizen, Inc.; Central Virginia Educational Television; Virginia Commonwealth University (Columbus, Ohio : Charles E. Merrill Pub. Co., 1976)
Deals with the reality of multiple involvement with the child with the developmental disabilies, the rationale for early identification and intervention, procedures for securing services, and the child's right to an education
Keywords: Handicapped children -- Education; Child study; Child development deviations -- Diagnosis